Pengendalian Ulat Daun Sawi ( Crocidolomia binotalis Zell.) dengan Insektisida Organik - Santosa, Sartono Joko (Innofarm:Jurnal Inovasi Pertanian, 2011)
Abstract A research carried out from 26 th August untill 1 th October 2010 in Mayoretno village, Matesih district, Karanganyar regency at the elevation of 500 meters above sea levels. The aim of the research to controle attact Caterpillar Leaf Worm Crop Mustard ( Crocidolomia binotalis Zell.)with Organic Insecticide The research method used Randomized Completely Block Design (RCBD) with ten treatmens and three replications, are : control,  Beauveria bassiana 7,5 cc/l ; 15 cc/l; 22,5 cc/l concentration; Extract Mahkota Dewa seed1,5 cc/l; 3 cc/l; 4,5 cc/lconcentration and  extract mimba seed 1 cc/l; 2 cc/l; 3 cc/l  concentration. The data were analysed using an Analysis of Variance and Duncans Multiple Range Test 5%. Beauveria bassiana with 22,5 cc/l concentration Insecticide is proven effective insecticide can give storey level death of highest larva 44,19 % and this effect lowest intencity caterpillar leaf worm 18,33 % so that can give highest weight consumtion per plant namely 184,56 g. Key words : Controle , Caterpillar Leaf Worm, Crop Mustard, Organic Insecticide